Bentuk dan Sebaran Lesi Demodekosis pada Sapi Bali (THE SHAPE AND DISTRIBUTION OF DEMODECOSIS LESIONS ON BALI CATTLE) - Suartha, I Nyoman; Septyawati, Reny; Gunata, I Ketut (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
Demodicosisis a skin diseasecaused byDemodexsp., that inhabits animal hair folliclesandcandamageskintissue. This study aims to reveal the form and distribution of demodicosis lesions in Bali cattle in thecenter of breeding bali cattle Sobangan. The sample was recorded based on the present of skin lesions.Skin scraps were collected, and examined for Demodex sp. The shape of the lesions was documented byobserving existing lesions on the body of bali cattle. The size of the lesions was measured using calipers.The distribution of the lesions was done by dividing the body area of head, neck, back, and abdomen region.We found that the prevalence of demodicosis was 12.66% (38/300). The shape of demodicosis lesions werenodular, scab, and dollar plaque. Distribution of demodicosis lesions was mostly at the neck (36.8%), atthe back (34.21%), and neck to back (23.68%). In conclusion, the prevalence of demodicosis was mild, andthe greatest distribution was on neck. In order to reduce the incidence rate in bali cattle should be keptproperly and sanitation is carried out at a good standard.
Keywords: demodekosis, bali cattle, skin lesion